631 Multiwave Locked System LASER photobiomodulation in the multidisciplinary team approach/ management of a 3rd degree burn on the posterior thorax in an 82-year-old woman – a case study (Balneo and PRM Research Journal, 2024)
Introduction: In the current study, we aim to demonstrate the efficacy and significance of MLS LASER therapy in the context of post-combustion injuries, through the expeditious improvement of a harmonious healing process for the lesions. A burn is recognized as a significant concern in the medical field [1], as the majority of them are profoundly disabling [2] and negatively impact crucial facets of daily existence, as well as overall quality of life [3]. Material and methods:  We hereby present the case of an 82-year-old female patient admitted to our Neuromuscular Rehabilitation Clinic Division following a post-burn incident that occurred in January 2023, characterized by flame burns of IIA-IIB-III degrees on the posterior thorax, bilateral arms, and sacral regions. Initially, the patient received care in the Plastic Surgery Clinic Division of our hospital, and after three weeks, she was transferred to our division. Here, she underwent a tailored rehabilitation program and received notable Multiwave Locked System (MLS) LASER treatment on the posterior thoracic region over ten sessions. The patient’s progress was comprehensively and objectively quantified using assessment scales. Results: Remarkable results were obtained, consisting a significant reduction in the size of the lesion on the posterior thoracic region after 10 sessions of MLS LASER photobiomodulation, along with a related improvement in locomotor and self-care dysfunctions. Conclusions:  Since references in the literature regarding the use of this type of phototherapeutic intervention are relatively scarce, we consider this case study to contribute to a better understanding and appreciation of it. At the same time, an efficient multidisciplinary collaboration proves advantageous not only for the patient’s well-being, but also for the development of current therapeutic interventions, contributing to the enrichment of this complex domain. Keywords: Burns, Multiwave Locked System (MLS) LASER photobiomodulation, Multidisciplinary team, Burn rehabilitation program.